2019
DOI: 10.1093/mnras/stz2047
|View full text |Cite|
|
Sign up to set email alerts
|

An empirical infrared transit spectrum of Earth: opacity windows and biosignatures

Abstract: The Atmospheric Chemistry Experiment's Fourier Transform Spectrometer on the SCISAT satellite has been measuring infrared transmission spectra of Earth during Solar occultations since 2004. We use these data to build an infrared transit spectrum of Earth. Regions of low atmospheric opacity, known as windows, are of particular interest, as they permit observations of the planet's lower atmosphere. Even in the absence of clouds or refraction, imperfect transmittance leads to a minimum effective thickness of h mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…These data can be converted into exoplanet-like transit spectra, as described by Robinson et al 41 and demonstrated by Macdonald and Cowan. 42 Measurements of Earth occultations of stars with a variety of stellar types would yield further detail on Earth's atmosphere and allow us to build a database of star-planet observations to compare with exoplanet transmission spectroscopy.…”
Section: Earth Occultations Of Solar System Planets and Bright Starsmentioning
confidence: 99%
“…These data can be converted into exoplanet-like transit spectra, as described by Robinson et al 41 and demonstrated by Macdonald and Cowan. 42 Measurements of Earth occultations of stars with a variety of stellar types would yield further detail on Earth's atmosphere and allow us to build a database of star-planet observations to compare with exoplanet transmission spectroscopy.…”
Section: Earth Occultations Of Solar System Planets and Bright Starsmentioning
confidence: 99%
“…However, correct interpretation of all of these data relies upon models of planetary processes that are best developed and validated using in situ or remote‐sensing observations of Solar System bodies (Fujii et al., 2014). Similarly, observations of Solar System bodies, even very fundamental ones like phase‐dependent photometry of the Jovian planets (Mayorga et al., 2016), or simulated transmission observations of Titan (Robinson, Maltagliati, et al., 2014) or the Earth (Macdonald & Cowan, 2019) can help inform planning and interpretation of exoplanet observations and help us train predictive (forward) and retrieval (inverse) models for exoplanets.…”
Section: Exoplanets and Observablesmentioning
confidence: 99%
“…Transmission spectra for the Earth have generally been achieved through indirect means, by observing solar occultations (e.g. Macdonald & Cowan 2019) or via a tertiary body reflecting the filtered starlight (e.g. Pallé et al 2009;Vidal-Madjar et al 2010;Ugolnikov et al 2013;Arnold et al 2014;Yan et al 2015;Kawauchi et al 2018;Youngblood et al 2020).…”
Section: Transiting Exoplanet Geometry and Subsequent Biosignature De...mentioning
confidence: 99%